2014
DOI: 10.3346/jkms.2014.29.3.334
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of a Korean Translation of the ASAS Health Index and Environmental Factors in Korean Patients with Axial Spondyloarthritis

Abstract: The objective of this study was to develop a Korean version of the Assessment of Spondyloarthritis International Society-Health Index/Environmental Factor (ASAS HI/EF) and to evaluate its reliability and validity in Korean patients with axial spondyloarthritis (SpA). A total of 43 patients participated. Translation and cross-cultural adaptation of the ASAS HI/EF was performed according to international standardized guidelines. We also evaluated validity by calculating correlation coefficients between the ASAS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
3
2
0
2
Order By: Relevance
“…In addition, we identified the frequency of each item on the ASAS HI questionnaire in Korean patients with axSpA. Similar to previous studies, we found correlations between ASAS HI and existing axSpA disease parameters including BASDAI, ASDAS, and BASFI [3,4,18]. Finally, for the first time, predictors of ASAS HI were identified in patients with axSpA and subgroups of patients with AS and nr-axSpA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, we identified the frequency of each item on the ASAS HI questionnaire in Korean patients with axSpA. Similar to previous studies, we found correlations between ASAS HI and existing axSpA disease parameters including BASDAI, ASDAS, and BASFI [3,4,18]. Finally, for the first time, predictors of ASAS HI were identified in patients with axSpA and subgroups of patients with AS and nr-axSpA.…”
Section: Discussionsupporting
confidence: 81%
“…A total of 17 dichotomous items pertaining to pain, emotional functioning, sexual functioning, mobility, self-care, and even community life were ultimately selected [1]. ASAS HI was validated internationally in 23 countries including patients with axial and peripheral SpA and has been translated into 18 languages, including Korean [3,4]. The ASAS HI questionnaire is easy to complete by choosing either “I agree” or “I do not agree”, and it has high internal consistency [4].…”
Section: Introductionmentioning
confidence: 99%
“…The psychometric properties of this Spanish-language version of the ASAS-HI were consistent with the results found in the original study [ 6 ], and also with the study of the validity of the Korean-language translation [ 17 ]. Similarly, an Italian study also have confirmed the reliability, feasibility and validity of the ASAS-HI [ 18 ].…”
Section: Hisupporting
confidence: 87%
“…В настоящем исследовании показано, что индекс здоровья ASAS связан с активностью заболевания и функциональным статусом пациентов со СпА, что согласуется с данными других исследователей и подтверждает валидность опросника [20][21][22]. В ходе исследования мы продемонстрировали взаимосвязи между значениями ASAS HI и параметрами КЖ больных по SF-36.…”
Section: Discussionunclassified
“…Это, скорее всего, объясняется вспомогательным характером ASAS EF Items Set, дополняющим ASAS HI. Аналогичные данные получены при валидации индекса в других странах [15,[20][21][22].…”
Section: Discussionunclassified